2020
DOI: 10.3390/ijerph17041421
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Carious Lesions in Permanent First Molars in Children: A Seven-Year Retrospective Cohort Study

Abstract: The aim of this study was to evaluate the risk factors associated with the occurrence of caries in permanent teeth (PT) and in the permanent first molar (PFM) seven years after their eruption. Children born in 2005 who were enrolled in a Community Dental Program were included. A total of 278 children were enrolled. Evaluated risk factors were parental caries experience, educational level of the mother, routine medications, systemic diseases, dietary habits, toothbrushing frequency, existence of molar incisor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…For this sample, it was found that toothbrushing with fluoridated toothpastes once or more a day had a significant association (p = 0.035) and positive correlation with the AHS. This result is similar to that of the study of Llena et al 34 where it was found that toothbrushing with fluoridated toothpastes at least twice a day was associated with significantly lower values of DMFT. On the one hand, toothbrushing by itself is not as effective to control lesion progression 35 , nonetheless it is important to consider its effect on the disorganization and removal of the dental biofilm, which allows salivary clearance of accumulated harmful compounds (acids) and reduction of bacterial mass density.…”
Section: Discussionsupporting
confidence: 91%
“…For this sample, it was found that toothbrushing with fluoridated toothpastes once or more a day had a significant association (p = 0.035) and positive correlation with the AHS. This result is similar to that of the study of Llena et al 34 where it was found that toothbrushing with fluoridated toothpastes at least twice a day was associated with significantly lower values of DMFT. On the one hand, toothbrushing by itself is not as effective to control lesion progression 35 , nonetheless it is important to consider its effect on the disorganization and removal of the dental biofilm, which allows salivary clearance of accumulated harmful compounds (acids) and reduction of bacterial mass density.…”
Section: Discussionsupporting
confidence: 91%
“…Carious lesions are formed due to changes occurring in the biofilm and thus disturbances in the neutral environment of the oral cavity, causing the demineralization of enamel [5]. Apart from the patient's hygiene and dietary habits, other factors, such as medication and systemic diseases, that may affect saliva secretion are also important in the development of caries [6]. Additionally, periodontal diseases with alveolar bone destruction appear as a result of dysbiosis, often in patients with an impaired host response [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the pathologies found in the oral cavity, dental caries is the most prevalent, chronic, and non-communicable disease worldwide [ 7 , 8 , 9 ]. The World Health Organization (WHO) indicates that 60–90% of children are affected by dental caries [ 10 ], with this being one of the main causes of premature tooth loss in children, causing damage to the primary dentition and future permanent dentition [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caries is defined as a sugar-dependent disease that causes the destruction of dental tissue due to the presence of organic acids that are produced by cariogenic bacteria located in the dental biofilm, added to an imbalance in the remineralization and demineralization process over time [ 1 , 9 , 12 , 13 ]. In addition, other factors are involved in the development of new caries lesions and the progression of existing ones, such as the susceptibility of the host, dental hygiene, frequency of dental check-ups and behavioral, social and/or cultural factors [ 7 , 13 ]. It represents a public health problem and affects the quality of life of the child, and can cause problems in development, growth, and learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation